2005
DOI: 10.1007/s00299-005-0971-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly efficient, repetitive system of organogenesis in soybean (Glycine max (L.) Merr).

Abstract: A highly efficient, repetitive system of organogenesis was developed in soybean. Seeds of soybean cv. 'White hilum' pretreated with TDZ formed multiple bud tissue(s) (MBT) at the cotyledonary nodes. MBT initiation occurred only if the axillary buds were not removed from the cotyledonary node. The best MBT formation was achieved by pretreating the seeds for 1 week on medium supplemented with 0.1 mg/l TDZ, followed by culture of the cotyledonary node on medium supplemented with 0.5 mg/l BA for 4 weeks. Culture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
4
25
0
Order By: Relevance
“…It was observed that exogenous cytokinin application alters axillary meristem development, promotes shoot proliferation and regeneration of the cell in meristemic tissues. This phenomenon has been reported previously in cytokinin pretreated seedlings (Shan et al, 2005). The results reported in this study are also in agreement with previous studies suggesting soybean organogenesis by continuous culture on BAP containing medium (Wright et al, 1987) or by culturing in alternative cycle of BAP and TDZ (Barwale and Widholm, 1990) or combination of BAP with auxin mainly 2,4-D or NAA (Tripathi and Tiwari, 2003;Radhakrishnan and Ranjithakumari, 2007) or ZTR for plant regeneration (Kamenicka et al, 1998;Steinitz et al, 2006;Barik et al, 2007) either through organogenesis, callogenesis or protoplast culture.…”
Section: Iv) Rooting (Stage Iv)supporting
confidence: 89%
See 1 more Smart Citation
“…It was observed that exogenous cytokinin application alters axillary meristem development, promotes shoot proliferation and regeneration of the cell in meristemic tissues. This phenomenon has been reported previously in cytokinin pretreated seedlings (Shan et al, 2005). The results reported in this study are also in agreement with previous studies suggesting soybean organogenesis by continuous culture on BAP containing medium (Wright et al, 1987) or by culturing in alternative cycle of BAP and TDZ (Barwale and Widholm, 1990) or combination of BAP with auxin mainly 2,4-D or NAA (Tripathi and Tiwari, 2003;Radhakrishnan and Ranjithakumari, 2007) or ZTR for plant regeneration (Kamenicka et al, 1998;Steinitz et al, 2006;Barik et al, 2007) either through organogenesis, callogenesis or protoplast culture.…”
Section: Iv) Rooting (Stage Iv)supporting
confidence: 89%
“…They reported that by the treatment of BAP, the cells in embryonic axes do not remain quiescent and are reprogrammed to produce multiple somatic foci. However, addition of thidiazuron (TDZ) (Franklin et al, 2004;Shan et al, 2005) or kinetin (Ma and Wu, 2008) with BAP has been reported as better combination for embryoid formation from cotyledonary node explants. Radhakrishnan and Ranjithakumari (2007) produced callus from mature half seed's nodal segment using different combinations of BAP and 2,4 dichloro phenoxy acetic acid (2,4-D).…”
mentioning
confidence: 99%
“…The highest mean number (7.93) of shoots per explant was obtained from double cotynode explant treated with 2 mg L -1 BA. Shan et al (2005) obtained a maximum of 6 shoots per explant when explants were treated with 0.1 mg L -1 TDZ. Their explants were the cotyledonary nodes, with the epicotyl, hypocotyl and cotyledons removed.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports show the effect of PGRs such as (GA 3 ) on seed germination, seedling growth and crop yield (Malik and Saxena, 1992;Zhang et al, 1999;Hamayun et al, 2010). Few link seed hormonal treatment to multiple shoot induction (Shan et al, 2005;Ma and Wu, 2008). According to our study, although the presence of cytokinins in the germination medium had no effect on the in vitro soybean germination; seedling growth was affected by higher concentrations of BA (2-4.00 mg L -1 ) resulting in development of thicker seedlings which proved to be a better source for excisions of explants for multiple shoot induction in comparison to seedlings developed on PGR free-medium.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that BAP, the cells in embryonic axes do not remain quiescent and are reprogrammed to produce multiple somatic foci. In addition of TDZ (thidiazuron) or Kn + BAP showed better performance on embryoids formation from cotyledonary node in soybean (Shan et al 2005, Ma andWu 2008).…”
Section: Introductionmentioning
confidence: 99%